2018
DOI: 10.1186/s13065-018-0451-0
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of N- (4-bromophenyl)-1- (3-bromothiophen-2-yl)methanimine derivatives via Suzuki cross-coupling reaction: their characterization and DFT studies

Abstract: A variety of imine derivatives have been synthesized via Suzuki cross coupling of N-(4-bromophenyl)-1-(3-bromothiophen-2-yl)methanimine with various arylboronic acids in moderate to good yields (58–72%). A wide range of electron donating and withdrawing functional groups were well tolerated in reaction conditions. To explore the structural properties, Density functional theory (DFT) investigations on all synthesized molecules (3a–3i) were performed. Conceptual DFT reactivity descriptors and molecular electrost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…This experiment yielded the imine hydrolysis product. In the 3rd set, a Schiff base without a pyridine group was utilized for the Suzuki coupling, which yielded a non-hydrolysis product, as shown in Scheme 2 and reported by our group [22].…”
Section: Resultsmentioning
confidence: 99%
“…This experiment yielded the imine hydrolysis product. In the 3rd set, a Schiff base without a pyridine group was utilized for the Suzuki coupling, which yielded a non-hydrolysis product, as shown in Scheme 2 and reported by our group [22].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Peter Langer and his co-workers reported the direct arylation of pyrazole via Suzuki-Miyaura cross-coupling [5]. Moreover, our research group reported the direct arylation of thiophene and discussed the antibacterial and anti-urease activity of 2-aryl-3-methyl-5-arylthiophenes [6,7]. Previously, the arylation and biological activities of thiophene amide derivatives were also reported by our research group [8].…”
Section: Introductionmentioning
confidence: 81%
“…The mixture was kept on stirring at reflux for more than 20 h. After cooling to normal temperature, the reaction mixture was filtered with solvent ethyl acetate and then concentrated under reduced pressure. The resulted products were purified with column chromatography (n-hexane/ethyl acetate, 75:25) [ 58 , 59 , 60 , 61 , 62 , 63 ]. The final products ( 4a – 4n ) were dried, recrystallized and finally analyzed with NMR and mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%